Physical and geomechanical properties of the Siwalik sandstones, Amlekhganj-Suparitar area, central Nepal Himalaya - Tamrakar, Naresh Kazi; Yokota, Shuichiro; Shrestha, Suresh Das (Journal of Nepal Geological Society, 2002)
The Siwalik Group, one of the world's largest fluvial deposits, distributed in the fore deep basin of the rising Himalayas, crops out well in Central Nepal. The group comprises of mudstones, sandstones and conglomerates ranging in age from middle-Miocene to early Pleistocene. Sandstones form the major lithology in the Siwalik Group and distributed pervasively. Forty-four samples of sandstones were tested for physical and geomechanical properties in order to create a database on Siwalik sandstones and to know the variability of these properties with respect to their stratigraphic levels. Dry density and saturated density of sandstones are 2.10-2.63 g/cm3 and 2.22-2.66 g/cm3, respectively. Porosity is found to vary between 1.93 and 15.2%.They bear weak to strong uniaxial compressive strength (1.29-51.6 MPa), very low to high point load strength (0.05-4.53 MPa, measured across bedding), high deformability (secant modulus =0.03-0.98 GPa and tangent modulus = 0.06-1.09)and low modulus ratio (17.8-86.6). The Schmidt hammer hardness in sandstones ranges from 12 to 52. Variation of these properties is independent of stratigraphic level. Dry density and porosity correlate well with uniaxial compressive strength, point-load strength and modulus ratio, and bear highly significant relationships. Hence, dry density and porosity can be used for predicting strength measures for the Siwalik sandstones.